An Access Control with Face Recognition Based on LBPH Algorithm - Bakan, Salih Emre; Yildirim, Merve (Ieee, 2025)
This study presents an access control system based on facial recognition using the Local Binary Pattern Histogram (LBPH) algorithm. The system is designed to enhance security by verifying individuals through facial features instead of traditional access methods such as passwords or keycards. The LBPH algorithm is employed due to its robustness in handling variations in lighting and facial expressions. Besides, a Haar Cascade method is used for face detection and histogram equalization to increase the image quality. After obtaining successful recognition, an access control is realized by an Arduino-controlled locking mechanism that activates a servo motor. Thus, by utilizing these image processing techniques in a real-time system, a robust and efficient system is designed for access control. The study explains the architecture of the system, the implementation process, and experimental results, demonstrating its efficiency in real-world applications. As a result, it is observed that the LBPH algorithm provides a reliable and accurate face recognition, making it a proper choice for access control applications.
7th Global Power Energy and Communication Conference-GPECOM-Annual -- JUN 11-13, 2025 -- Bochum, GERMANY
Keywords: face recognition; LBPH algorithm; Haar Cascade method; access control system; security; image processing